A critical evaluation of the 1964 preferencial agreement (Labour agreement) for Mozambique mineworkers in the light of the South Africa - Mozambique DTC and the SADC treaty - Bugan, Noel Arnold (Department of Finance and Tax, 2017)
In 1964, a labour agreement was signed between the governments of South Africa and Portugal on behalf of its colony, Mozambique, to regulate the migration of Mozambican mineworkers to South African mines. In terms of this agreement the Mozambican mineworkers who received income on the South African mines were exempt from any taxes on their South African source income. Although outdated, the agreement is still in force today and is used by the South African mines to enter into employment contracts with Mozambican mineworkers. Many countries in the SADC region enter into double taxation agreements for the avoidance of double taxation. The 1964 labour agreement is quite unique as the income received by the Mozambican mineworkers is exempt from tax in South Africa for the duration of the contract (usually up to 18 months) entered into by the Mozambican mineworkers and their South African employers although the source of income is in South Africa. The challenge is whether this agreement should continue as an international agreement and whether it is discriminatory to exempt these mineworkers when compared to other mineworkers in the same position working in South Africa. The purpose of this study is to examine the application of this labour agreement with reference to the South African Income Tax Act and the double tax agreement with Mozambique. It further questions whether this agreement causes a revenue loss and whether or not such loss is justifiable. It further tests whether this agreement is a tax incentive and whether or not it leads to harmful tax competition in violation of the SADC agreement. Finally, the agreement is assessed in light of the discrimination article in the double tax agreement and based on section 9 of the Constitution of the Republic of South Africa. The main conclusion is whether the 1964 labour agreement should continue as an international agreement in the present circumstances as the agreement is fairly outdated and subject to various interpretations which will have an effect on revenue loss to the South African fiscus.